Influence Of Financial Literacy and Financial Technology To Investment Decision Student at University Of Bhayangkara Jakarta Raya - Desy Novitasari; Ari Sulistyowati (Draf Solusi Indonesia, 2023)
This study aims to determine whether there is an intermediate effectfinancial literacy andfinancial technology toinvestment decision students at University of Bhayangkara Jakarta Raya. the results of this study indicate thatfinancial literacy (X1) has a significant effect oninvestment decision students. This proves that the level of financial literacy of a student is the basis for consideration in making investment decisions.financial technology positive effect oninvestment decision students. This shows that the availability of technology in financial terms, especially investment applications from PT Phintraco influences the decisions of students in investing. From the results of the F test, financial literacy andfinancial technology simultaneously a positive effect oninvestment decision students. This shows that a student's decision to invest requires adequate financial literacy and adequate investment technology.